Encyclopedia of Catholic social thought, social science, and social policy - Coulter, Michael L. 1969- (Gale virtual reference library, 2007)
Combines theoretical work on important topics and scholarly disciplines; social science perspectives on a variety of topics; and treatment of practical policy implications that flow from applying the Catholic religious, moral, and intellectual tradition to contemporary issues.